Annual review of United Nations affairs 1966-1967 - Richard N. Swift; New York University. Graduate Program of Studies in United Nations and World Affairs; Institute for Annual Review of United Nations Affairs (New York : University Press, 1968)
Contains the proceedings of the 1st- Institute for Annual Review of United Nations Affairs, New York University, 1949-
Includes bibliographical References and Index.
Vols. for <1977- > issued in parts.
Vols. for 1949- issued by the New York University Graduate Program of Studies in United Nations and World Affairs in cooperation with the Dept. of Public Information of the United Nations.
1949-1965/66, in 1965/66.
Has occasional special supplement, 1958: Chronology of the United Nations; 1964- : Chronology and fact book of the United Nations.
Keywords: United Nations -- Periodicals